Analisis Tingkat Kepuasan Masyarakat pada Pelayanan Puskesmas Pembantu Sidorame Timur Kecamatan Medan Perjuangan - Nur Rizky Arini Lubis; Susilawati Susilawati (Jurnal Health Sains, 2022)
The satisfaction of the community around the health institution is the most important element in health services. Communities around health service agencies will feel satisfied when they feel good and fast service. One that will affect the level of satisfaction is the way health workers interact with the community. The purpose of this study was to determine the level of satisfaction of the community around the UPT Puskesmas Pembantu Sidorame Timur, Medan Perjuangan District, with the services provided. This research is descriptive using survey method where the number of samples using simple random sampling so that the sample is 30 people with data analysis method using univariate analysis to describe all variables. So the results of this study are that the majority of people feel less satisfied by 50%, quite satisfied by 23.3%, satisfied by 20%, and very satisfied by 6.7%. So it can be concluded that the community is not satisfied with the health services at the UPT Puskesmas Pembantu Sidorame Timur, Medan Perjuangan District.